The Pilates method improves the relationship agonist-antagonist flexor and extensor knee in elderly: a randomized controlled trial. - Oliveira, Laís Campos de; Oliveira, Raphael Gonçalves de; Pires-Oliveira, Deise Aparecida de Almeida (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Due the increase in elderly population, a increase concern in considering factors that can contribute to healthy aging. The muscle strength of the lower limbs and the improvement of the agonist-antagonist relationship and knee extensor and flexors, enable greater independence in older people. Objective: To investigate the effects of Pilates method in agonist-antagonist relationship in knee extensor and flexor in healthy older women. Methods: Thirty-two elderly woman were randomly divided into two groups. Experimental group (EG, n = 16, 63.62 ± 1.02 years) and control group (CG, n = 16, 64.21 ± 0.80). Isokinetic evaluation of the knee extensors and flexors was held at 180°/s, pre and post-intervention, considering the agonist-antagonist ratio (%). The experimental and control groups participated of Pilates sessions and static stretching, respectively, twice a week for 12 weeks. To verify the normality of the data was used the Shapiro-Wilk test followed by the Student t test to compare the differences between the pre and post evaluation (p <0.05). Results: It was possible to identify a statistically significant improvement in agonist-antagonist relationship between the pre and post-intervention only for the GE (p <0.005) for both the right lower limb and for left lower limb. Conclusion: The Pilates method improves the relationship agonist-antagonist of the knee extensor and flexor muscles after 12 weeks of intervention. Registro Brasileiro de Ensaios Clínicos: RBR-472p29.